DINAMIKA PSIKOLOGIS REMAJA DALAM RUANG LINGKUP KELUARGA DISFUNGSIONAL YANG MENGALAMI KEKERASAN EMOSIONAL - Ade Saputra; Gefira Adias Permata, Syfa Salsa Azahra, Sulistiasih (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to identify the social impacts experienced by a child who is a victim of Domestic Violence (KDRT) and provide equal attention to children as members of the nation. The research method used is qualitative with a case study type, which examines the condition of the object naturally with the researcher as the key instrument. Data were collected through triangulation, and data analysis was inductive, emphasizing meaning over generalizations. The research results show that domestic violence has a significant impact on children's character education, because children learn and imitate the violent behavior they witness. Poverty is a complex problem across time, especially in the modern era, where urbanization is one of the causes of poverty in cities.